College for convicts: the case for higher education in American prisons - Zoukis, Christopher (McFarland, 2014)
Why do we care? -- A historical perspective on prison education -- Prison education today : a reality check -- Barriers to betterment : roadblocks in the cell block -- Oases in the desert -- Options for distance learning -- Too late, too old? -- No guts, no gain -- What the world knows -- Thinking inside the box to make it happen -- Appendices: Federal bureau of prisons program statements -- Prisoner publications and pen-pal clubs -- Funding for correctional education -- Free and discounted books for prisoners -- Federal financial aid for incarcerated individuals FAQ -- Numbers tell a story -- Prison education in Europe -- Reentry facts